Linkages between sediment composition, wave climate and beach profile variability at multiple timescales - Harshinie Karunarathna (Marine Geology, 2016)
The paper analyses, compares and contrasts cross-shore morphodynamic behaviour of four diverse beaches that have very different regional settings, wave climates and sediment characteristics, with the aid of rarely available long term measurements of beach profiles and incident waves. The beaches investigated are Narrabeen Beach, New South Wales, Australia; Milford-on-Sea Beach, Christchurch Bay, UK; Hasaki Coast, Ibaraki Prefecture, Japan; and Joetsu-Ogata Coast, Niigata Prefecture, Japan. A statistical analysis, equilibrium beach profile analysis and Empirical Orthogonal Function analysis are used to investigate, compare and contrast spatial and temporal variability of cross shore beach profiles of the selected beaches at short-, medium- and long-term timescales. All beaches show evidence of multi-timescale morphodynamic change. Narrabeen Beach profile has the highest sensitivity to local weather patterns. Milford-on-Sea, Joetsu-Ogata and Hasaki profiles are sensitive to seasonal variation of the wave climate however, they also show some correlations with regional climate variabilities. The nature of sediment exchange across the profile, which contributes to profile shape change with time, is found to be related to sediment characteristics across the profile. At Milford-on-Sea and Joetsu-Ogata, both of which have composite profiles, sediment exchange between the upper beach and the inter-tidal zone dominates profile change, irrespective of the distinct differences in sediment composition found in the two beaches. On the other hand in Narrabeen and Hasaki where beach sediment comprises medium to find sand, sediment exchange and hence profile change occur mainly in intertidal and subtidal zones.